Energy expenditure is increased in kidney transplant patients. - Christophe Montaurier; Anne-Eisabeth Heng; Noel Cano; Nicolas Caillot; Adeline Blot; Nathalie Meunier; Béatrice Morio (The Korean Society of Nephrology, 2012)
After kidney transplantation weight gain is associated with adverse effects such as hypertension, dyslipidemia, insulin resistance, increased vascular risk and deterioration of graft function. The identification weight gain mechanisms would be helpful to propose preventive strategies. This study addressed energy expenditure (EE) changes after kidney transplantation. Fifteen male patients aged 52.8±1.7 years, transplanted for one to 6 years, non-diabetic and with stable renal function (calculated creatinine clearance, 30-90 ml/min/1.73 m²) were included. They received anticalcineurin drugs but not corticosteroids. Nine healthy volunteers matched for age (54.2±1.9 years) and fat-free mass (FFM) were considered as controls. Body composition, including FFM, was determined by DEXA. EE was measured under controlled conditions (24 hours in calorimetric chambers) during the following activities: sleep, rest, meals, and 2 sessions of 30 min of treadmill walking (4 and 5 km/h). The EE results are expressed per kg of FFM, mean ± SEM. FFM was respectively 62.0±2.3 and 62.3±2.7 kg in patients and controls (NS). EE during sleep was 15% higher in patients than in controls (4.37±0.10 vs. 3.80±0.24 kJ/hour/kg FFM, p<0.05). The 24h-EE also tended to be higher in patients compared to controls (+8%, p=0.057,158.31±3.90 vs. 146.13±4.35 kJ/day/kg FFM). No significant difference was observed between patients and controls for the EE during walking at 4 or 5 km/h, during meals and at rest. In conclusion, in kidney transplant patient weight gain occurs despite hyper-metabolism during sleep and over 24 h. Mechanisms of weight gain therefore possibly involve changes in food intake and/or spontaneous physical activity.